1995
DOI: 10.1176/ps.46.8.774
|View full text |Cite
|
Sign up to set email alerts
|

Contact between psychotherapists and psychiatric residents who provide medication backup

Abstract: Several steps are necessary to optimize communication between treating clinicians and documentation of such communication. They include initial contact to discuss the treatment contract and clarify each clinician's responsibilities, formal written consent from the patient, regular contacts between clinicians to discuss the patient's progress, and collaboration between clinicians on the patient's treatment plan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Hernandez and Doherty (2005) stated that U.S. SFT practice patterns indicated that a majority of therapists treated clients who were prescribed PM. In studies that explored clinicians' interactions with a provider who prescribed PM to a mutual client, the highest reported rate of communication between mental health and medical providers occurred in approximately half of the cases (Godfrey, 2011; Hansen‐Grant & Riba, 1995; Kalman et al, 2012; Mintz, 2005; Springer & Harris, 2010). The need for mental health providers to collaborate with prescribing providers was identified many decades ago (Druss & Goldman, 2018).…”
Section: Review Of Literaturementioning
confidence: 99%
“…Hernandez and Doherty (2005) stated that U.S. SFT practice patterns indicated that a majority of therapists treated clients who were prescribed PM. In studies that explored clinicians' interactions with a provider who prescribed PM to a mutual client, the highest reported rate of communication between mental health and medical providers occurred in approximately half of the cases (Godfrey, 2011; Hansen‐Grant & Riba, 1995; Kalman et al, 2012; Mintz, 2005; Springer & Harris, 2010). The need for mental health providers to collaborate with prescribing providers was identified many decades ago (Druss & Goldman, 2018).…”
Section: Review Of Literaturementioning
confidence: 99%
“…However, before 2010, only one study had investigated whether such communication actually takes place. Hansen-Grant and Riba’s survey ( Hansen-Grant and Riba, 1995 ) quantified communication between psychiatric residents prescribing medication and the institutional psychotherapists. They reported infrequent, poorly documented communication, and the absence of recorded patient consent for communication between providers.…”
mentioning
confidence: 99%